Investigating fiscal and monetary policies coordination and public debt in Kenya: Evidence from regime-switching and self-exciting threshold autoregressive models - William Irungu Ng'ang'a; Julien Chevallier; Simon Wagura Ndiritu (Kiel Institute for the World Economy (IfW), 2019)
This study explored the nature of fiscal and monetary policy coordination and its impact on long-run sustainability in Kenya. The study employed annual time series data from 1963 to 2014. Two objectives were investigated. (i) The determinants ofmonetary and fiscal policy rules under different policy regimes. (ii) The nature of fiscal and monetary policy regimes coordination in Kenya. Markov switching models were used to determine fiscal and monetary policy regimes endogenously. The fiscal policy regime was regarded as passive if the coefficient of debt in the MS model was significant and negative. This fiscal policy regime is regarded as unsustainable since the rise in debt is associated with a deterioration of the fiscal balance. On the other hand, the active monetary policy is synonymous with contractionary monetary policy since real in interest rate reacts positively to an increase in inflation. Robust analysis conducted using self-exciting threshold models confirms that monetary and fiscal policy reaction functions are nonlinear. The study findings show that passive or unsustainable fiscal regime was more dominant over the study period. There is evidence to support coordination between fiscal and monetary policy. There is a tendency for monetary policy to actively and prudently respond to unsustainable fiscal policy. Secondly, monetary policy sequentially responds to fiscal policy. The study recommended the adoption of systematic monetary response to a periodic deviation of fiscal policy from a long-run sustainability path.
http://dx.doi.org/10.7910/DVN/H8DSEG
Keywords: E62; F30; H61; 330; policy regimes; fiscal and monetary policy management; Markov-switching; SETAR